2014
DOI: 10.1016/j.biopsych.2013.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of COMT Haplotypes and Psychosis Risk in 22q11.2 Deletion Syndrome

Abstract: Background 22q11.2 deletion syndrome (22q11.2DS) is the most common genetic syndrome associated with schizophrenia. The catechol-o-methyltransferase (COMT) gene is located in the obligatory deletion region, and possible associations between COMT variants and neuropsychiatric manifestations in 22q11.2DS have been reported. The purpose of the current study was to evaluate the effect of COMT hemizygosity and molecular haplotypes on gene expression and enzyme activity and its association with psychotic symptoms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 41 publications
1
51
0
Order By: Relevance
“…For example 25–30% of adult patients with 22q11.2 deletion syndrome (DiGeorge Syndrome), a deletion which includes the COMT gene – of relevance for dopamine metabolism (Gothelf et al, 2014) – suffer from schizophrenia (Murphy et al, 1999), making this one of the highest-penetrance genetic changes involved in schizophrenia to date. Other CNVs have also been identified which are significantly associated with schizophrenia (Kirov et al, 2014).…”
Section: The Genetics Of Schizophreniamentioning
confidence: 99%
“…For example 25–30% of adult patients with 22q11.2 deletion syndrome (DiGeorge Syndrome), a deletion which includes the COMT gene – of relevance for dopamine metabolism (Gothelf et al, 2014) – suffer from schizophrenia (Murphy et al, 1999), making this one of the highest-penetrance genetic changes involved in schizophrenia to date. Other CNVs have also been identified which are significantly associated with schizophrenia (Kirov et al, 2014).…”
Section: The Genetics Of Schizophreniamentioning
confidence: 99%
“…Additionally, unmasking of other sequence variants throughout the genome and/or in the non-deleted allele that may affect the activities of the gene products has also been hypothesized to contribute to the variability of features for 22q11.2 deletions [Brzustowicz and Bassett, 2012;Zarchi et al, 2013;Carmel et al, 2014;Gothelf et al, 2014;Radoeva et al, 2014]. Other studies have suggested a possible gender effect in proximal deletion subjects, owing to the interaction of estrogen with COMT , but additional studies are needed to clarify whether there is indeed a relationship in DGS patients [Coman et al, 2010;Yu et al, 2012].…”
Section: Variability Of Phenotypementioning
confidence: 99%
“…The convergence of associations of both psychotic and cognitive phenotypes with this particular SNP might speak to correlations between these dependent variables in VCFS but is particularly interesting, given recent evidence for an enrichment of SNPs associated with diminished cognitive aptitude in schizophrenia (9), and forwards the possibility that, in the context of VCFS, functional common variation in COMT might be an important predictor of neuropsychiatric outcomes. However, as noted by Gothelf et al , (7) their data suggest that the molecular impact of the implicated SNP requires further study to clarify its mechanism of action. For example, the distinguishing effect of this SNP was in the expression of an extended alternate transcript, and its prediction of enzymatic activity was dependent on the status of other COMT markers that were not associated with the clinical variables.…”
mentioning
confidence: 84%
“…The new findings of Gothelf et al (7), identifying messenger RNA expression, protein function, and clinical effects of SNPs in the remaining COMT allele in 22q11.2 deletion syndrome, take a step toward answering these questions. By cross-leveraging both multiple common/small effect size and rare/large-effect size variation, the work accomplishes a significant elaboration of COMT biology, demonstrating complex, multi-locus interactions at the cellular level and addressing the important conundrum of incomplete penetrance in VCFS.…”
mentioning
confidence: 99%